Acute degradation of nucleolin reveals its novel functions in cell cycle progression and cell division in triple negative breast cancer. - Mills, Joseph.; Tessari, Anna.; Anastas, Vollter.; Sunilkumar, Damu.; Samadi Rad, Nastaran.; Lamba, Saranya.; Cosentini, Ilaria.; Reers, Ashley.; Zhu, Zirui.; Miles, Wayne O; Coppola, Vincenzo.; Cocucci, Emanuele.; Magliery, Thomas J; Shive, Heather.; Davies, Alexander E; Rizzotto, Lara.; Croce, Carlo M; Palmieri, Dario. (Tufts University. Tisch Library., 2025)
Keywords: Nucleolin, NCL, Cell cycle, Auxin-inducible degron.; Springer Open.